Hubungan Faktor Asupan Gizi Terhadap Kejadian KEK Pada Ibu Hamil Dipuskesmas Gedeg - I Wayan Murtiyasa; Putu Gana Cahya Narta Putra; Putu Wahyu Semara Gita; Reyza Salam Asmara; Didik Sarudji (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2022)
Mojokerto Regency is one of the districts with a high number of pregnant women who experience chronic energy deficiency (KEK) and continues to increase every year. Chronic energy deficiency is a nutritional problem due to lack of food consumption and energy sources containing micronutrients. Though the intake of quality nutrition in sufficient quantities is needed for the health of pregnant women and the fetus in the womb. Therefore, this study aims to analyze whether there is a relationship between nutritional intake and the incidence of KEK in pregnant women at the Gedeg Mojokerto Health Center. Where the independent variable in this study is nutritional intake in pregnant women and the dependent variable is KEK in pregnancy. The design in this study was a cross sectional survey and the population was all pregnant women in the working area of Gedeg Mojokerto Health Center with a total sample of 75 respondents. The data from this study were processed using the Chi-square statistical test which was then followed by the Odds Ratio test. And from the results of the study, it was found that there was a significant relationship between nutritional intake of pregnant women and the incidence of KEK (Chronic Energy Deficiency) in the Puskesmas Gedeg Mojokerto, this was evidenced by the acquisition of a p-value of 0.000 (< 0.05) which was further emphasized. with the results of the Odds Ratio (OR) which obtained a value of25.227 (> 1), where pregnant women with poor nutritional intake had a 25.227 times greater risk of experiencing KEK (Chronic Energy Deficiency) than pregnant women with good nutritional intake.